Low-fat and high-fat dairy products are differently related to blood lipids and cardiovascular risk score. (December 2014) - Kai, Samantha Huo Yung; Bongard, Vanina; Simon, Chantal; Ruidavets, Jean-Bernard; Arveiler, Dominique; Dallongeville, Jean; Wagner, Aline; Amouyel, Philippe; Ferrières, Jean
Background: Fat content of dairy foods is diverse, potentially leading to varying effects on cardiovascular risk. We studied relationships of low- and high-fat dairy products with lipids and level of cardiovascular risk (assessed by the SCORE equation), in a cross-sectional population survey conducted in three French areas. Subjects and methods: A sample of 3078 participants aged 35–64 years underwent a standardized cardiovascular risk assessment. Subjects were asked to record the types and amounts of foods and beverages they consumed over a three-consecutive-day period. Dairy products were separated into two groups: the low-fat group comprised milk (including milk in desserts and beverages), yogurts and cottage cheese, whereas other cheeses formed the high-fat group. Results: After adjustment (including physical activity and a diet quality score), the probability of an increased cardiovascular mortality score (≥1%) decreased from the lowest to the highest quartile (Q) of low-fat dairy intake: odds ratio (OR) ORQ1 = 1; ORQ2 = 0.89 (95% confidence interval: 0.73–1.10), ORQ3 = 0.78 (0.63–0.97) and ORQ4 = 0.68 (0.55–0.85) for the first, second, third and fourth quartile, respectively. Results were notably different for high-fat dairy intake: ORQ2 = 1.02 (0.82–1.25); ORQ3 = 0.90 (0.73–1.11); ORQ4 = 1.07 (0.86–1.32). Intake of low-fat dairy products was inversely associated with low-density lipoprotein cholesterol (LDL-C), but no significant independent relationship was found with high-density lipoprotein cholesterol (HDL-C) or triglycerides. None of the lipid parameters was significantly associated with the consumption of high-fat dairy products. Conclusion: Participants with the highest intake of low-fat dairy products had the lowest mortality risk score and exhibited the best LDL-C profile. Such favourable associations were not observed with cheese consumption.